(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Protein deficiency remains one of the major global challenges in ensuring food security. According to the Food and Agriculture Organization (FAO), the growing world population, environmental constraints, and rising costs of livestock feed are expected to substantially increase the demand for nutritive proteins in the coming decades. In this context, identifying sustainable, renewable, and environmentally friendly biomass sources is of great scientific and practical value. One of the most promising candidates among such resources is the microalga Chlorella vulgaris.Chlorella is a unicellular green microalga known for its exceptionally high nutritional value, rapid growth, and rich biochemical composition. Often referred to as a “superfood,” this microalga contains a diverse range of bioactive compounds essential for human health. The chemical profile of Chlorella demonstrates a high nutritive potential: its dry biomass consists of 40–55% high-quality protein, 30–35%